Transportation Problem in Rapidly New Town Development Area - BS Kusbiantoro (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
Jabotabek region is an area of 6580 km2 with a population more than 20 million. In the year 2010, Jabotabek is estimated to have more than 29 million population. For the last ten years, the role of private developers has increased sharply in this region. They have proposed and started to develop new towns and industrial estates ranging from 700 ha to 6000 ha covering an area of more than 43000 ha. This rapid new town development, however, has not been followed and facilitated with the needed infrastructure. The government regulations require only the private developers to provide internal or local facilities and services for the new development. This in turn may create major problem at regional level, such as traffic congestion, flooding, water shortage etc. This is what this paper would like to address, i.e. how serious the problem will be